Zawiyet Umm el-Rakham - Snape, S. R.
"The site of Zawiyet Umm el-Rakham, on Egypt's Mediterranean coast 300 km west of Alexandria, was one of the largest and most important of the fortresses built by Ramesses II. It was constructed in order to protect Egypt's trade links in the Eastern Mediterranean and to guard Egypt itself from the invasions of Libyan tribesmen. The site was briefly investigated by the archaeologist Labib Habachi in the 1950s and, since 1994, has been the subject of a major archaeological project under the auspices of the University of Liverpool, led by Dr. Steven Snape"--Author's website.